2007
DOI: 10.1136/jcp.2005.036038
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MSH2 protein expression is a risk factor in early stage cervical cancer

Abstract: Background: Loss of mismatch repair (MMR) gene expression has been associated with fewer metastases and improved prognosis in various tumour types. Aims: To evaluate the predictive and prognostic significance of loss of MMR protein MSH2 in early stage cervical cancer. Methods: Specimens from 218 consecutive patients with early stage, surgically treated cervical cancer were analysed. Median age was 42 years (interquartile range 35-53). International Federation of Gynecology and Obstetrics (FIGO) stages were IB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“… 10 12 According to prior studies, lack of MSH2 or/and MLH1 is a common phenomenon in cervical intraepithelial neoplasia and cervical cancer. 13 , 14 The MSI of cervical cancer was 6.1% in this study, which was consistent with the report by Ercoli et al, 15 but was less than the 12.6% reported by Baay et al 16 We reason that the source of cases and single-nucleotide-repeat markers may lead to these variations. In the study, the ratio of dMMR was 25.8% and the rates of dMMR varied greatly when analyzed in subtypes with different childbearing history, abortion history, and tumor differentiation.…”
Section: Discussionsupporting
confidence: 91%
“… 10 12 According to prior studies, lack of MSH2 or/and MLH1 is a common phenomenon in cervical intraepithelial neoplasia and cervical cancer. 13 , 14 The MSI of cervical cancer was 6.1% in this study, which was consistent with the report by Ercoli et al, 15 but was less than the 12.6% reported by Baay et al 16 We reason that the source of cases and single-nucleotide-repeat markers may lead to these variations. In the study, the ratio of dMMR was 25.8% and the rates of dMMR varied greatly when analyzed in subtypes with different childbearing history, abortion history, and tumor differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…DNA mismatch repair proteins were found as important GOBP. Among these proteins, we found MSH2 which is among the routine IHC markers to identify microsatellite instability . Interestingly, its loss of expression is usually a risk factor in early stage cervical cancer .…”
Section: Resultsmentioning
confidence: 90%
“…We concluded that TMA samples are a good representation of the full sections and therefore useful as a research tool in the screening of markers for their predictive and prognostic potential. 22 Immunostaining was semiquantitatively scored based on the intensity of nuclear or cytoplasmic staining. Intensity of immunostaining for receptor expression was scored as negative (0), weak (1+), positive (2+), or strongly positive (3+) staining.…”
Section: Analysis Of Immunostaining On Tmamentioning
confidence: 99%